Biotelemetry and Computer Analysis of Electrocardiograms - Amlinger, P. R. (Methods of Information in Medicine, 1969)
Routine transmission of electrocardiograms and their computer interpretation via long-distance telephone lines has been proven feasible in the Automated Electrocardiogram Project of the Missouri Regional Medical Program. Though this Pilot Project — the first on a state-wide basis — is still viewed as an applied research effort rather than a service, such biotelemetry is rapidly gaining acceptance as a medium to bring modern medicine, through modern technology, to urban and remote rural areas as well, where it is most needed.The computer executes all the wave measuraments and calculations with incredible speed. It takes over a most boring, repetitive part of the physician’s work. However, it can only follow the instructions of the diagnostic program, compiled by expert cardiologists. Thus, it is an ever-ready, never-tiring servant for the physician and his patients.